Preparation and Properties of Amorphous Calcium Phosphate/Multi(amino Acid) Copolymer Composite for Bone Repair - Shao, H.B.; Yao, Y.M.; Zhang, L.; Zhang, Q.F.; Li, H. (Asian Journal of Chemistry, 2014)
In the present study, a novel bioactive composite composed of amorphous calcium phosphate (ACP) and multi (amino acid) copolymer (MAC) was fabricated for bone repair and characterized. The results show that the compressive strength of the ACP/MAC composites was in the range of 72-96 MPa, increased with an increase in the amorphous calcium phosphate content. The composite was degradable and kept a sustain degradation rate with the weight loss of 65-84 w % after soaking in phosphate buffered saline (PBS) for 24 weeks, significantly increased with an increase in the ACP content. In vitro MG63 cell co-culture experiments showed that the composite shows good cytocompatibility and thus allows cells to adhere, proliferate and differentiate.